تأثير بعض العوامل اللاحيوية في ديناميكية مجتمعات الحشرة القشرية الحمراء Aonidiella aurantii (Maskell) في بساتين الحمضيات (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
The California red scale Aonidiella aurantii (Maskell) (Hemipter: Diaspididae), is one of the most important citrus pests in Syria. Our aim was to study the population dynamics of A. aurantii from May 2018 to January 2019 in four citrus orchards located in Lattakia governorate (Western Syria). The A. aurantii populations had, on the branches, one peak phase in Al-Sarsakia and Al-Bassah orchards in November 2018 and January 2019, respectively, and tow peak phases in Al-Ramah (in October 2018 and January 2019) and Menjela (in Septemper 2018 and January 2019) orchards. However, one peak phase was observed on the fruits during the autumn months in all orchards. The number of A.aurantii continued to increase at temperatures ranging from 12.8Cº to 30Cº, and reached at the peak with relative humidity 66%. تعد الحشرة القشرية الحمراء  Aonidiella aurantii (Maskell) (Hemiptera: Diaspididae) من أهم الآفات التي تصيب الحمضيات في سورية. هدف هذا البحث إلى دراسة ديناميكية مجتمع A. aurantii ضمن أربع بساتين حمضيات تابعة لمنطقتي اللاذقية والحفة، خلال الفترة الممتدة من أيار 2018 وحتى كانون الثاني 2019. كانت منحنيات ديناميكية أعداد الحشرة على الأفرع، وحيدة القمة في بستاني السرسكية والبصة (تشرين الثاني2018 وكانون الثاني2019 على التوالي)، وثنائية القمة في بستاني الرامة (تشرين الأول2018وكانون الثاني2019) ومنجيلا (أيلول2018 وكانون الثاني2019). بينما كانت وحيدة القمة على الثمار في جميع البساتين وذلك خلال أشهر الخريف. استمرت أعداد الحشرة بالتزايد عند درجات حرارة تراوحت من 12.8 وحتى 30Cº، كما بلغت ذروتها عند درجة رطوبة نسبية 66%.